POSSIBLE COMPLEXES OF THREE-DIMENSIONAL PLANES IN PROJECTIVE SPACE P6. II - Nersesian, V. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
In the work possible complexes of three-dimensional planes in six-measured projective space P6 are studied. It’s proved that one-parametric family of cones of second order with three-dimensional flats forming and univariate top which describes unfold surface defines four-parametric possible family of planes E3, which are all three-dimensional forming to this cones. It’s also proved that if we take in space P6 our-parametric family of three-dimensional planes including fixed straight line l and touching two hypercone with one general univariate top l we will get possible family of three-dimensional planes. Corresponding family tangent of four-parametric family is formed by intersection of tangent hyperplanes to the cones in the sport of osculation of three-dimensional planes family with them.